A Juridical Review of Debtor Default in Consumer Financing Agreements at Financing Companies - Wanda Pitaloka (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to legally analyze debtor default in consumer financing agreements at financing companies. The method used is normative juridical with a statutory and conceptual approach. The results show that the financing agreement is the basis of the legal relationship between creditors and debtors, which gives rise to rights and obligations for the parties according to the Civil Code. Default occurs when the debtor fails to fulfill its obligations, such as late or non-payment of installments. As a result, the creditor has the right to collect, issue a summons, and even execute fiduciary guarantees. Dispute resolution is, in principle, prioritized through non-litigation channels to reach a mutual agreement.